20.9k views
5 votes
Re-write the quadratic function below in Standard Form
y=-3 (x - 2)² – 7

User Guinn
by
5.6k points

1 Answer

1 vote

Answer:


y=-3x^2+12x-19

Explanation:

we know that

The quadratic equation in standard form is equal to


y=ax^(2) +bx+c

we have


y=-3(x-2)^(2)-7

This is a quadratic equation in vertex form

Convert to standard form


y=-3(x^2-4x+4)-7

Apply distributive property


y=-3x^2+12x-12-7

Combine like terms


y=-3x^2+12x-19 ----> quadratic equation in standard form

User MobX
by
5.4k points